2014
DOI: 10.1155/2014/987690
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Vendor Based on Intuitionistic Fuzzy Analytical Hierarchy Process

Abstract: Business environment is characterized by greater domestic and international competitive position in the global market. Vendors play a key role in achieving the so-called corporate competition. It is not easy however to identify good vendors because evaluation is based on multiple criteria. In practice, for VSP most of the input information about the criteria is not known precisely. Intuitionistic fuzzy set is an extension of the classical fuzzy set theory (FST), which is a suitable way to deal with imprecisene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 29 publications
0
18
0
2
Order By: Relevance
“…Research in [41] shows combining AHP with fuzzy theory can focus on relative importance in evaluation criteria than the logic of human thinking. The fuzzy AHP method can help the decisionmaker to make a realistic and flexible decision based on the criteria and alternatives [42]. In this subsection, fuzzy AHP was developed to find the goal.…”
Section: Stage 4 Fuzzy Ahp As Decision-making Of Design Bapv Systemmentioning
confidence: 99%
“…Research in [41] shows combining AHP with fuzzy theory can focus on relative importance in evaluation criteria than the logic of human thinking. The fuzzy AHP method can help the decisionmaker to make a realistic and flexible decision based on the criteria and alternatives [42]. In this subsection, fuzzy AHP was developed to find the goal.…”
Section: Stage 4 Fuzzy Ahp As Decision-making Of Design Bapv Systemmentioning
confidence: 99%
“…Pitchipoo & Rajakarunakan, 2013 ; Kaur, 2014;Merry et al, 2014;Patil & Kant, 2014;Stevic et al,2016;Rouyendegh & Erkan, 2011;Shahroudi et al, 2011;Boran et al,2009. (2) dengan I = 1,2, .., m; dan j= 1,2, …, n ; c. Menentukan matriks solusi ideal positif dan matriks solusi ideal negatif, Solusi ideal positif A+ dan solusi ideal negatif A-dapat ditentukan berdasarkan rating bobot ternormalisasi menggunakan bobot dari hasil pengujian dengan AHP (y ij ) sebagai : Pada pengolahan data terakhir dilakukan pengujian nilai preferensi antara kriteria dengan alternatif supplier terpilih di PT XYZ dengan menggunakan metode TOPSIS.…”
Section: Kajian Pustakaunclassified
“…In recent years, this problem has been handled using various mathematical tools. Some of the recent research in this area can be found in [32][33][34][35][36][37][38].…”
Section: Illustrative Examplementioning
confidence: 99%